American Visions of the Netherlands East Indies/Indonesia US Foreign Policy and Indonesian Nationalism, 1920-1949 - Gouda, Frances (American Studies, 2002)
The authors of this book challenge the view that was current among many people in the Netherlands during the period 1945-1949 that the American government and its foreign policymakers unequivocally backed the Indonesian Republic's struggle for independence. The same myth of America's political endorsement of Indonesians' quest for independence continues to reverberate in the United States itself. In fact, ex-President Clinton repeated the story as recently as 1995 when he wrote to ex-President Suharto that in the post-World War II era, President Truman and the U.S. Congress had actively supported Indonesia 'as the nation was being born'. On the basis of research in American, Indonesian, Dutch, and Australian diplomatic records and in the archives of the United Nations, Gouda and Brocades Zaalberg describe and analyze American visions of the Dutch East Indies/Indonesia from the 1920s to December 1949, when the Kingdom of the Netherlands relinquished its sovereignty over the archipelago in southeast Asia to the United States fo Indonesia. Their historical analysis suggests that the American diplomatic establishment was not as ignorant of conditions in the Indonesian archipelago as many Dutch people assumed, both before and after World War II. They also chronicle the unfolding of America's steady but tactic backing of its faithful Dutch ally in northern Europe until early 1949, when U.S. assessments of the regions in the world where the Cold War might ignite into a 'Hot War' began to incorporate the anti-colonial, nationalist struggles in Indonesia and Vietnam.